What Role Does Trabecular Bone Score Play in Chronic Inflammatory Rheumatic Diseases? - Ruaro, Barbara; Casabella, Andrea; Molfetta, Luigi; Salton, Francesco; Confalonieri, Paola; Confalonieri, Marco; Baratella, Elisa; De Tanti, Antonio; Bruni, Cosimo (Frontiers in Medicine, 2020)
Patients suffering from rheumatic inflammatory diseases, e.g. systemic sclerosis, rheumatoid arthritis and ankylosing spondylitis, are at risk of low bone mass. Dual-energy X-ray Absorptiometry (DXA) is the traditional radiological measurement technique for bone mineral density (BMD). The recently developed trabecular bone score (TBS) enhances the skeletal information provided by standard BMD. It re-analyzes the spatial dynamics of pixel intensity changes in lumbar spine DXA images, defining a quantitative index, characterizing trabecular bone microarchitecture. It has been demonstrated that low TBS values are associated with an increased incidence of fractures in patients with rheumatic diseases. These methods used together for bone damage evaluation can be of value to identify individuals who will potentially fracture. The main scientific literature on the clinical aspects of osteoporosis, including the use of TBS in evaluating this pathology, are herein reported aimed at shedding light on the role trabecular bone score plays in chronic inflammatory rheumatic diseases.